2022
DOI: 10.7150/jca.65421
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis identifies FAM49B as an immune-related prognostic maker for hepatocellular carcinoma

Abstract: Family with sequence similarity 49, member B (FAM49B) is highly expressed in many tumors, its role in malignant tumors especially in hepatocellular carcinoma (HCC) remains uncertain. We first evaluated the expression, clinical features, and prognostic value of FAM49B using RNA-seq and clinical data from The Cancer Genome Atlas. We further assessed the role of FAM49B in the tumor immune microenvironment. The correlation of FAM49B with the sensitivity of 192 anti-cancer drugs was analyzed using data from Genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…12C, http://links.lww.com/HEP/H887). A previous study showed that FAM49B upregulation was associated with poorer prognosis in patients with HCC 27 . To this end, we analyzed the clinical significance of LANCL1 and FAM49B co-expression.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…12C, http://links.lww.com/HEP/H887). A previous study showed that FAM49B upregulation was associated with poorer prognosis in patients with HCC 27 . To this end, we analyzed the clinical significance of LANCL1 and FAM49B co-expression.…”
Section: Resultsmentioning
confidence: 98%
“…A previous study showed that FAM49B upregulation was associated with poorer prognosis in patients with HCC. 27 To this end, we analyzed the clinical significance of LANCL1 and FAM49B co-expression. We defined high and low LANCL1 or FAM49B expression by T/NTL > 2 and T/NTL ≤ 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Cyrib gene resides on human chromosome 8q24, near c-Myc, and is frequently amplified in many types of cancer, including pancreatic cancer ( Nikolaou and Machesky, 2020 ). High expression of CYRI-B correlates with poor outcome in many cancers ( Li et al, 2021 ; Xu et al, 2022a ), including in human pancreatic cancer. To further investigate a potential role for Cyrib in pancreatic cancer, we first assessed the expression of CYRI-B in the KPC mouse model of metastatic PDAC ( Hingorani et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Cyri-b gene resides on human chromosome 8q24, near c-Myc, and is frequently amplified in many types of cancer, including pancreatic cancer (Nikolaou & Machesky, 2020). High expression of CYRI-B correlates with poor outcome in many cancers (Li et al , 2021; Xu et al , 2022a), including in human pancreatic cancer. To further investigate a potential role for cyri-b in pancreatic cancer we first assessed the expression of CYRI-B in the KPC mouse model of metastatic PDAC (Hingorani et al ., 2005).…”
Section: Resultsmentioning
confidence: 99%